Digital inequality, faculty communication, and remote learning experiences during the COVID-19 pandemic: A survey of U.S. undergraduates - Katz, Vikki S.; Jordan, Amy B.; Ognyanova, Katherine (PloS one, 2021)
The COVID-19 pandemic forced closure of most U.S. university campuses in March 2020, obliging millions of students to finish their semesters via remote learning. This study examines whether and how students' prior and current experiences of digital inequality-defined as constrained access to the internet and internet-connecting devices-were associated with their remote learning experiences. An anonymous, online survey of 2,913 undergraduate college students from 30 U.S. universities completing their spring term remotely was conducted between April and May 2020. Hypothesis testing utilized a structural equation model with cluster-bootstrapped standard errors and p-values, to account for students being clustered by university. Findings revealed that students' challenges with internet connectivity and digital devices during remote learning were associated with lower remote learning proficiency (RLP). Difficulty communicating with professors and teaching assistants was also associated with lower RLP. Prior experience with online coursework was associated with higher RLP, and digital inequality challenges during the year prior to the pandemic with lower RLP. Moreover, students who reported greater financial hardship since the start of the pandemic experienced significantly more connectivity, device, and faculty communication challenges during remote learning, and had significantly lower RLP. Many students will continue to learn remotely in some form until the pandemic recedes. We identify key factors associated with students' remote learning proficiency: (1) consistent, high-speed internet connectivity and functioning devices to connect to it, and (2) the ability to relate to and communicate easily with professors and teaching assistants. This study identifies potential barriers to effective remote learning, as well as possible opportunities to improve students' experiences.